2007
DOI: 10.1016/j.virol.2007.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular targeting and interactions among the Potato virus X TGB proteins

Abstract: Potato virus X (PVX) encodes three proteins named TGBp1, TGBp2, and TGBp3 which are required for virus cell-to-cell movement. To determine whether PVX TGB proteins interact during virus cell-cell movement, GFP was fused to each TGB coding sequence within the viral genome. Confocal microscopy was used to study subcellular accumulation of each protein in virus-infected plants and protoplasts. GFP:TGBp2 and TGBp3:GFP were both seen in the ER, ER-associated granular vesicles, and perinuclear X-bodies suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 71 publications
10
74
2
4
Order By: Relevance
“…We were unable to detect BSMV TGB1 binding by using yeast two-hybrid analyses (Table 1), but BSMV TGB1 interactions were revealed by the use of experimental approaches differing from those used previously with potato mop-top virus (PMTV), PSLV, and PVX (9,23,34). We first obtained direct evidence for in vivo TGB1 binding by chemical cross-linking experiments.…”
Section: Discussionmentioning
confidence: 95%
“…We were unable to detect BSMV TGB1 binding by using yeast two-hybrid analyses (Table 1), but BSMV TGB1 interactions were revealed by the use of experimental approaches differing from those used previously with potato mop-top virus (PMTV), PSLV, and PVX (9,23,34). We first obtained direct evidence for in vivo TGB1 binding by chemical cross-linking experiments.…”
Section: Discussionmentioning
confidence: 95%
“…The 8 kDa PVX TGB3 is an ER-binding protein with a single, N-terminal transmembrane domain (Morozov & Solovyev, 2003;Verchot-Lubicz et al, 2007), and TGB2 and TGB3 are reported to co-localize (Ju et al, 2008;Solovyev et al, 2000). PVX TGB3 interacts with the ER network and is associated with granular vesicles induced by TGB2 (Samuels et al, 2007). The 7 kDa TGB3 of AltMV is similar in size to that of PVX (Hammond et al, 2006), but appears to behave differently.…”
Section: Introductionmentioning
confidence: 99%
“…We then tested their possible association with two other organelles, Golgi and peroxisomes. To this end, we co-expressed pREP 1-207 -GFP with either pDsRED-ST (marker for Golgi; Samuels et al, 2007) or pRTL2-MFP-RFP (marker for peroxisome), followed by microscopic observations. It was clear that these punctate bodies colocalized neither with Golgi ( Fig.…”
Section: A Subdomain In the Mtr Determines The Formation Of Punctate mentioning
confidence: 99%